THE IMPACT OF FORGIVENESS ON EARLY ADULTS WHO ARE VICTIMS OF PARENTAL DIVORCE - Johanna, Petra; Gresia Natalia Hutagalung; Dhia Christine Nataline; Rina Mirza (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2026)
Divorce often leaves wounds or deep trauma that affects the emotional development and social relationships of children into adulthood. These wounds can cause heartache or resentment which can affect the psychology of the victim of divorce. This research aims to investigate the impact of forgiveness from parental divorce on early adults. The research method used is qualitative with a case study approach through in-depth interviews with four female respondents aged 20–24 who experienced parental divorce in childhood. The results of the study found that the causes of divorce were domestic violence, infidelity, and poor communication. The psychological impacts included trauma, lack of self-confidence, loss of a father figure, verbal and physical violence, difficulties in establishing social and romantic relationships, and economic difficulties. Two respondents experienced verbal violence because their faces resembled their father's, with different perpetrators of violence being their mother and grandmother. This study also found that respondents were able to achieve forgiveness through four main phases: the uncovering phase, the decision phase, the work phase, and the deepening phase. One respondent experienced the uncovering phase twice due to divorce and the death of her father. Two of the respondents achieved forgiveness due to religious influence, while others did so through consultation with psychologists and psychiatrists, as well as support from friends, and the families of both their father and mother.